Herbal medicines for cancer cachexia: protocol for a systematic review. Issue 6 (3rd June 2014) - Park, Bongki; Jun, Ji Hee; Jung, Jeeyoun; You, Sooseong; Lee, Myeong Soo
Abstract : Introduction: To assess the efficacy of herbal medicines as a treatment of cancer cachexia. Methods and analysis: We will search the following 13 electronic databases from their inception. MEDLINE (PubMed), the Cochrane Central Register of Controlled Trials (CENTRAL), EMBASE, Allied and Complementary Medicine Database (AMED), China National Knowledge Infrastructure (CNKI), Wanfang, Journal Integration Platform (VIP) and six Korean Medical Databases (KoreaMed, the Korean Traditional knowledge Portal, OASIS, DBPIA, the Research Information Service System and the Korean Studies Information Service System) without restrictions on time or language. The data will be extracted independently by two authors using predefined criteria. Disagreements will be resolved by discussion between the authors. The risk of bias will be assessed using the Cochrane risk of bias tool. Dissemination: The review will be published in a journal. The review will also be disseminated electronically and in print. An update of the review will be conducted to inform and guide healthcare practice and policy. Trial registration number: PROSPERO 2013:CRD42013006612.